WISATA KULINER DAN GAYA HIDUP MASYARAKAT KONSUMSI PADA ERA DIGITAL: ANALISA TEOLOGIS DENGAN PERSPEKTIF BUDAYA POPULER - Hendra Putra (Jurnal Teologi Cultivation, 2019)
AbstractSociety is becoming increasingly consumptive. Consuming goods is notbecause of the value of its use, but for the sake of lifestyle, so that humans today are never able to meet their needs. To understand the consumption society, the writer examines in a qualitative research with exploratory description method. Research Objectives: Strive for the theological values of Christianity to be interacted with popular culture specifically culinary tourism and the lifestyle of the consumption society in the fourth industrial revolution era (digital era). Thus the results of the study, namely: The development of popular culture does not actually deceive humans, but rather empowers in relation to the cultural mandate.Keywords: Society, consumption, popular culture, digital age, greed, andfragility